Practical grounding, bonding, shielding and surge protection - Vijayaraghavan, G. (Practical professional books from Elsevier., 2004)
This book will allow you to gain practical skills and know-how in grounding, bonding, lightning & surge protection. Few topics generate as much controversy and argument as that of grounding and the associated topics of surge protection, shielding and lightning protection of electrical and electronic systems. Poor grounding practice can be the cause of continual and intermittent difficult-to-diagnose problems in a facility. This book looks at these issues from a fresh yet practical perspective and enables you to reduce expensive downtime on your plant and equipment to a minimum by correct application of these principles. Learning outcomes: * Apply the various methods of grounding electrical systems * Detail the applicable national Standards * Describe the purposes of grounding and bonding * List the types of systems that cannot be grounded * Describe what systems can be operated ungrounded * Correctly shield sensitive communications cables from noise and interference * Apply practical knowledge of surge and transient protection * Troubleshoot and fix grounding and surge problems * Design, install and test an effective grounding system for electronic equipment * Understand lightning and how to minimize its impact on your facility * Protect sensitive equipment from lightning An engineer's guide to earthing, shielding, lightning and surge protection designed to deliver reliable equipment and communications systems that comply with international and national codes Discover how to reduce plant downtime and intermittent faults by implementing best-practice grounding/earthing techniques Learn the principles of cable shielding in communication networks.